Adverse drug reactions, multimorbidity and polypharmacy: a prospective analysis of 1 month of medical admissions - Girvan Burnside; Munir Pirmohamed; Rostam Osanlou; Dyfrig A Hughes; Lauren Walker (BMJ Open)
Objective To ascertain the burden and associated cost of adverse drug reactions (ADRs), polypharmacy and multimorbidity through a prospective analysis of all medical admissions to a large university teaching hospital over a 1-month period.Design Prospective observational study.Setting Liverpool University Hospital Foundation National Health Service (NHS) Trust, England.Participants All medical admissions with greater than 24-hour stay over a 1-month period.Main outcome measures Prevalence of admissions due to an ADR and associated mortality, prevalence and association of multimorbidity and polypharmacy with ADRs, and estimated local financial cost of admissions where an ADR was a contributing or main reason for admission with projected costs for NHS in England.Results There were 218 identified patient admissions with an ADR giving a prevalence of 18.4%. The majority of these (90.4%) were ADRs that directly resulted in or contributed to admission. ADRs thus accounted for 16.5% of total admissions. Those with an ADR were on average taking more medicines (10.5 vs 7.8, p<0.01) and had more comorbidities than those without an ADR (6.1 vs 5.2, p<0.01). Drugs most commonly implicated were diuretics, steroid inhalers, anticoagulants and antiplatelets, proton pump inhibitors, chemotherapeutic agents and antihypertensives. 40.4% of ADRs were classified avoidable or possibly avoidable. The mortality rate due to an ADR was 0.34%. The average length of stay for those with an ADR was 6 days. Direct 1-month cost to the Trust from ADR admissions was £490 716. Extrapolated nationally, the projected annual cost to the NHS in England is 2.21 billion.Conclusion The local prevalence of admission and mortality from ADRs is higher than previously reported. Important factors that could be contributing to this include polypharmacy and multimorbidity. ADRs place a significant burden on patients and healthcare services with associated financial implications. Reducing inappropriate polypharmacy should be a major aim for preventing ADRs.